Peer-leaders’ experiences and challenges in distributing HIV self-test kits in a rural fishing community, Rakai, Uganda - Matovu, Joseph K. B.; Nambuusi, Aminah; Wanyenze, Rhoda K.; Serwadda, David (BMC public health, 2021)
Distribution of HIV self-test kits by trained lay people in the community has resulted in increased uptake of HIV testing services among the targeted populations. However, little data exists on the experiences and challenges faced by trained lay people while distributing the kits. Methods: This qualitative study was conducted in Kasensero fishing community, Rakai, Uganda, in September 2019. We purposely selected 18 out of 34 peer-leaders that participated in a peer-led HIV self-testing intervention to participate in a post-intervention qualitative evaluation. The main intervention included identification and training of lay people in the community (‘peer-leaders’) to distribute HIV self-test kits to pre-selected members of their social network. Data for this study were collected at the end of the intervention. Data were collected on peer-leaders’ experiences in distributing the kits, challenges experienced during distribution and suggestions on how to improve peer-led HIV self-testing in typical fishing communities in the future. Data were analyzed manually following a thematic framework approach. Results: Of the 18 peer-leaders, eleven (61.1%) were aged 20–24 years while thirteen (72.2%) had secondary education. Most (n = 15) of the peer-leaders reported that they found it easier to distribute the kits to their social network members, with most of them distributing the kits at the social network members’ homes or at their own homes. HIV self-test kits were distributed at varying times (e.g. in the afternoon) depending on the agreement reached between the peer-leader and their social network member. A few peer-leaders reported that some of their social network members initially hesitated to accept the kits while other peer-leaders reported that they spent a ‘lot of time’ explaining the HIV self-testing procedures to some of their illiterate members. Peer-leaders argued for supervised HIV self-testing for illiterate people and the need to continuously follow-up social network members to check if they tested for HIV.
Keywords: HIV self-testing; Peer-leaders; Social network members